2017
DOI: 10.3769/radioisotopes.66.235
|View full text |Cite
|
Sign up to set email alerts
|

The Concentration Distributions of Cs in Soybean Seeds

Abstract: Radioactive materials, primarily radiocaesium (134 Cs+ 137 Cs), were released into the environment by the Fukushima Dai-ichi Nuclear Power Plant accident in March 2011. The proportion of the soybean plants that had an activity concentration of radiocaesium over 100 Bq/kg was higher than that of other crops. To examine the reason why the activity concentration of radiocaesium in soybeans was higher, the concentration distributions of Cs in soybean seeds were analyzed using two methods, X-ray fluorescence micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This may be due to the diff erence between paddy and fi eld soils, and also to the fact that soybeans accumulate a large amount of potassium in their seeds [16].…”
Section: Environmental Contamination | Soil Science | Atmospheric Chemistrymentioning
confidence: 99%
“…This may be due to the diff erence between paddy and fi eld soils, and also to the fact that soybeans accumulate a large amount of potassium in their seeds [16].…”
Section: Environmental Contamination | Soil Science | Atmospheric Chemistrymentioning
confidence: 99%
“…When the concentration distribution of Cs in soybean seeds were analyzed using radioluminography with RCs (Nihei et al 2017), it was found that Cs was uniformly distributed in the soybean seed, as was potassium, both of which likely accumulated in the cotyledon. The chemical behavior of Cs is expected to be similar to that of K because they are both alkali metal elements and have similar physicochemical properties.…”
Section: The Concentration Distribution Of Cs In Soybean Seedsmentioning
confidence: 99%